Complete feed batang pisang terfermentasi dengan level protein berbeda terhadap kecernaan bahan kering, kecernaan bahan organik dan TDN secara in vitro - Nurita Thiasari; Ahmad Iskandar Setiyawan (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The study aimed to investigate the effect of protein level in the complete feed based on fermented banana pseudostem(CFFBP) on in vitro digestibility. The experiment was conducted from May to August 2016. CFFBP was made at the field laboratory of Tribhuwana Tunggadewi University, Malang. Proximate and in vitro digestibility analysis was carried out at the Animal Nutrition Laboratory, the Faculty of Animal Husbandry, Brawijaya University. The experiment used Completely Randomized Design with 3 treatments and 5 replications. The treatments were P1CFFBP at protein level 12%; P2CFFBP at protein level 14%; P3CFFBP at protein level 16%. The results showed that digestibility of dry matter (DMD), digestibility of organic matter (OMD) and Total Digestible Nutrient (TDN) were significantly affected by the treatments (P<0.01). The highest digestibility of DMD, of OMD and TDN was found at CFFBP with protein level 14%. The DMD value were P171.56%, P2 75.06% and P3 74.32%. The OMD value were P165.53%, P2 68.50% and P3 69,82%. The TDN value were P161.84%, P2 66.07% and P3 64.91%. The experiment concluded that the increasing level of protein in the CFFBP could increase DMD, OMD and TDN, and it was related to the availability of protein and energy ratio. The ideal level of protein in this experiment was 14%. Keywords: complete feed, fermented banana pseudostem, in vivo digestibility, protein level